Distribution of biogenic silica in seafloor sediments on the East China Sea inner shelf: Seasonal variations and typhoon impact. (15th November 2018) - Li, Yunhai; Wang, Liang; Fan, Dejiang; Chen, Min; Lin, Yunpeng
Abstract: The content and distribution of biogenic silica (BSi) in sediments, as effective proxies for marine paleo-productivity and sedimentary environment evolution studies, has significant seasonal and event-based differences. Based on measurements of BSi content in the seafloor sediments acquired during three surveys in winter and before and after typhoons in summer in the Fujian-Zhejiang coastal mud deposition center (MDC-ZFC), respectively, the seasonal and event-based (typhoon process) differences of BSi in seafloor sediments are discussed by combining with data of the sediments grain sizes and the abundances of dominant diatom species. Conceptual models of the modern sedimentary environment (including BSi) are summarized. The study results show that the BSi in the seafloor sediments in the study region is relatively low, generally less than 1%. Generally, the BSi in the winter seafloor sediments is lower than that under normal summer sea conditions and the BSi in the sediments after the summer typhoons is higher than that under normal summer sea conditions. The differences in the origin of biogenic siliceous materials (seasonal growth of siliceous organisms) and the marine hydrodynamic environment (such as seafloor sediment resuspension and elutriation caused by strong marine hydrodynamic processes) are the major factors for different relative BSi content. The seasonal and event-based variations of BSi have important significance in paleo-oceanography and event sedimentology studies. Highlights: The content and distribution of BSi have seasonal and typhoon event differents. Plankton growth and sedimentary dynamics are control factors of BSi distribution. BSi studies have importance application in plaeoceanography sedimentology study.